2005
DOI: 10.1111/j.1365-2958.2005.04677.x
|View full text |Cite
|
Sign up to set email alerts
|

RecN protein and transcription factor DksA combine to promote faithful recombinational repair of DNA double‐strand breaks

Abstract: SummaryIn rapidly dividing bacterial cells, the machinery for repair of DNA double-strand breaks has to contend not only with the forces driving replication and transmission of the DNA but also its transcription. By exploiting I-Sce I homing endonuclease to break the Escherichia coli chromosome at one or more defined locations, we have been able to investigate how these processes are co-ordinated and repair is accomplished. When breaks are induced at a single site, the SOS-inducible RecN protein and the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 40 publications
(58 reference statements)
11
83
0
Order By: Relevance
“…NTHI0729 and NTHI0083 encode homologues of RecA and RecN. RecA and RecN have important roles in the repair of DNA damage which have been extensively characterized in UV damage experiments in many organisms, including E. coli and H. influenzae (43,50,51,77,82). Further repair mechanisms are potentially afforded by the gene products of NTHI0493 and NTHI0495, which encode homologues of the cochaperone proteins HscA and HscB, respectively, and that have roles in iron-sulfur cluster assembly (2,31,78).…”
Section: Resultsmentioning
confidence: 99%
“…NTHI0729 and NTHI0083 encode homologues of RecA and RecN. RecA and RecN have important roles in the repair of DNA damage which have been extensively characterized in UV damage experiments in many organisms, including E. coli and H. influenzae (43,50,51,77,82). Further repair mechanisms are potentially afforded by the gene products of NTHI0493 and NTHI0495, which encode homologues of the cochaperone proteins HscA and HscB, respectively, and that have roles in iron-sulfur cluster assembly (2,31,78).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, expression of RecN is highly regulated and is induced as part of the SOS response (8 -10). Based on this, it is thought unlikely that RecN has a role in the early steps of DSB repair (12,20). However, in both B. subtilis and D. radiodurans, RecN expression does not rely on a response to DNA damage, suggesting housekeeping roles for RecN in genome maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other members of the RecF pathway, recN mutants are quite sensitive to ionizing radiation or mitomycin C, and the repair of multiple, site-specific DSBs does not occur in the absence of RecN (8,12,13). The recN gene is also required for the suppression of chromosomal rearrangements and deletions (12) during the repair of a single DSB.…”
mentioning
confidence: 99%
“…The SOS-inducible RecN protein has structural similarities to proteins belonging to the SMC protein family, and is found to have a role in both the RecFOR and the RecBCD recombinational repair pathways (Grove et al, 2009;Lloyd et al, 1983;Picksley et al, 1984). When DNA breakage is induced at two or more distantly located sites, the presence of RecN protein is crucial (Meddows et al, 2005). Biochemical studies of purified RecN protein showed that the protein can stimulate intermolecular DNA interactions and has a weak ATPase activity (Grove et al, 2009;Reyes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%